Harmony Between The Values of and Tazkiyatun Nafs in Bugis Lontarak - Musyarif,; Yani, Ahmad; Umam, Fuadul; Anugrah,; Mako, Susi (Al-Hikmah, 2025)
This study explores the harmony between Bugis pappaseng values and the Islamic concept of tazkiyatun nafs. Using a qualitative library research approach combined with content analysis, the research examines lontarak manuscripts, historical sources, and classical Islamic texts on spiritual purification. The findings indicate that the five core values in pappaseng—lempu (honesty), amaccang (wisdom), asitinajang (propriety), agettengeng (steadfastness), and siri’ na pesse (honor and solidarity)—are aligned with fundamental principles of tazkiyatun nafs such as sidq (truthfulness), hikmah (wisdom), adl (justice), istiqamah (consistency), and ukhuwah (brotherhood). Both traditions emphasize moral integrity, social harmony, and spiritual devotion as foundations for individual and communal life. This research highlights that Bugis cultural heritage and Islamic teachings are not separate entities, but mutually reinforcing frameworks for shaping moral identity and sustaining collective values in contemporary society. Keywords: pappaseng, tazkiyatun nafs, Bugis ethics, Islamic spirituality